Biochemical and molecular evidence of a Δ9 fatty acid desaturase from Ensifer meliloti 1021 - Paulucci, Natalia Soledad (2014)
It has been reported that Ensifer meliloti presents a high proportion of monounsaturated fatty acids and has a putative desaturase gene designated as PhFAD12 (National Centre for Biotechnology Information), encoding a putative Δ12 desaturase-like protein. In this work, we report the desaturation capacity and characterisation of this gene encoding the putative fatty acid desaturase of E. meliloti 1021. This gene was also isolated from the rhizobial strain and overexpressed in Escherichia coli. Compared to a control, the expression of this gene in the transformed strain decreased the levels of palmitic and stearic acids, enhanced palmitoleic and cis-vaccenic levels, and allowed for the detection of oleic acid. E. coli overexpressing the putative desaturase gene was capable of desaturating palmitic and stearic acids to monounsaturated fatty acids, similarly to the rhizobial strain. Our studies show that AAK64726 encodes a Δ9 desaturase instead of a Δ12 desaturase as previously indicated. This work describes evidence for the presence of a desaturase-mediated mechanism in monounsaturated fatty acid synthesis in E. meliloti 1021, which is modified by high growth temperature. This mechanism supplements the anaerobic mechanism for unsaturated fatty acid synthesis.